The Influence of Employee Welfare Program on Work Productivity of Development Regional Bank Employees - Yohanes Paulus Luciany; Nurhayati; Arifuddin; Maiza Fikri; Prety Diawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Researchers want to know if employee welfare initiatives affect how productive employees are at work. The population for this study, which has 300 executive workers working in one of the branches of one regional bank in Indonesia, was sampled using a combination of convenience sampling and quota sampling approaches. With the use of SPSS for Windows 25.0, questionnaires and scales were used to gather data, which was then processed using basic linear regression analysis. The findings demonstrated that there is a substantial relationship between employee welfare programs and employee productivity, with the t value being significantly higher than the t table value and the significance value of 0.00 being lower than 0.05. Employee welfare initiatives impact job productivity by 50%.